Evaluating methodological approaches for measuring park accessibility: a meta-analysis - Harrell, Nathan (Kansas State University, 2023)
Inclusive parks are the most successful in serving communities. Park planning projects need to ensure that parks are equally accessible to all population groups. To determine if a park is accessible to all, several factors must be considered, including proximity of parks to users, community demographics, levels of service, and need. Historically, it is seen that marginalized communities typically do not have the same access to parks that are available to other parts of the community. To quantify the levels of accessibility, indices are used widely in park planning process. These indices consist of different measures related to park proximity, area, and surrounding demographic condition. There are different methods of quantifying accessibility using varying definitions of accessibility and data sources. These different accessibility measures and ways to calculate accessibility indices make the planners’ task difficult while using them for park planning and improvement projects. The goal of this meta-analysis is to explore the specific measures and methods used to assess accessibility in existing studies. This will allow planners to identify similarities and differences of measures considered within the landscape of park accessibility research. ParkScore, developed by the Trust for Public Land (TPL), attributes five main categories to the analysis of all parks: acreage, investment, amenities, access, and equity. Accessibility measures adopted by three other studies on park accessibility are evaluated and compared with the measures used for ParkScore. By classifying measures of the three studies within the five categories of the ParkScore analysis, it shows the commonalities and uniqueness of accessibility indices. All studies reviewed contain some measure of acreage, proximity access, and socio- economic equity. No other studies, besides ParkScore, considered investment as a measure of access. Only one study considered safety factors, and one study considered environmental factors. Variation in measures used for calculating accessibility indices are a result of different definitions of accessibility within the respective study. Planners need to be aware of these variations in park accessibility measures while working on any park planning project.
Keywords: Accessibility; Access; Equity; Parks